Struktury przyczynowo-skutkowe jako podstawa opracowania systemów wskaźników zrównoważonego rozwoju - Kusterka, Marta (Cause-Effects Relationships as a Pillars of Sustainable Development Indicators System, 2005)
The paper presents cause-effects relationships P-S-R, its particular modifications and sustainable development rules as a pillars of sustainable development indicators system. Another structure of indicators were presented in this study. The example of air quality indicators are included.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 92-99